Boosting the Potential for GeoDesign: Digitalisation of the System of Spatial Planning as a Trigger for Smart Rural Development - Marcin Wójcik; Karolina Dmochowska-Dudek; Paulina Tobiasz-Lis (Energies, 2021)
This article sought to present a process of abrupt transition where technological innovation is concerned. The matter taken up in particular was accelerating digitalisation, in the wider context of digital transformation, and in this case, in reference to spatial planning issues. This article offers an assessment of the level of digitalisation and digital transformation of spatial planning, with this, in turn, making it possible to define the potential at the disposal of rural areas, as they seek to bring in the idea of smart rural development. The empirical analyses present herein are founded upon secondary statistical data as well as our own primary data on the subject of geoportals and their functionality in rural parts of the Łódź region (Poland). The assessments of both planning coverage and geoportal functionality reported herein provide insight regarding the potential for rural areas to implement the concept of GeoDesign, as an integral part of “smart rural development”. The research carried out made it clear that only a fifth of rural gminas in the region are of high potential where GeoDesign is concerned, while every third gmina has only very low potential. A further key conclusion is that rural gminas heading along the path of “smart development” may break out of a spatial order existing thus far on the basis of disparities, and a division of regions into a centre and peripheries. This is of major significance in the context of the diffusion of innovation that digitalisation and digital transformation represent.